2011
DOI: 10.1111/j.1708-8208.2009.00183.x
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative Treatment of Peri-Implantitis Using Bone Substitutes and Membrane: A Systematic Review

Abstract: Purpose: This systematic review aimed to assess the available literature for regenerative treatment of peri-implantitis using bone graft substitutes and membranes. Methods: A search in electronic databases was conducted to assess all types of clinical studies treating bone defects derived from peri-implantitis using guided bone regeneration (GBR) techniques. Results: During the first screening, 399 titles were identified. Finally, 17 articles reporting on 173 implants were included. The articles mainly focused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 73 publications
5
80
2
1
Order By: Relevance
“…Barrier membranes are intended to stabilize the graft and to prevent epithelial downgrowth and fibroblast transgrowth into the grafted area, thereby favouring the population of bone cells in a bony defect. In agreement to findings in this review, Sahrmann et al [73] concluded that guided bone regeneration using both bone graft substitute and membrane represents the major part of published surgical regenerative treatment of peri-implantitis cases. Schwarz et al [27] stated that combination of biomaterial (bovine-derived xenograft) together with collagen membrane resulted in improved clinical outcomes compared to biomaterial (nanocrystalline hydroxyapatite) alone.…”
Section: Discussionsupporting
confidence: 90%
“…Barrier membranes are intended to stabilize the graft and to prevent epithelial downgrowth and fibroblast transgrowth into the grafted area, thereby favouring the population of bone cells in a bony defect. In agreement to findings in this review, Sahrmann et al [73] concluded that guided bone regeneration using both bone graft substitute and membrane represents the major part of published surgical regenerative treatment of peri-implantitis cases. Schwarz et al [27] stated that combination of biomaterial (bovine-derived xenograft) together with collagen membrane resulted in improved clinical outcomes compared to biomaterial (nanocrystalline hydroxyapatite) alone.…”
Section: Discussionsupporting
confidence: 90%
“…Unfortunately there is paucity of current literature comparing the effectiveness of various surgical techniques and grafting materials to treat periimplantitis. In addition, a recent systematic review found that there was only partial bone regeneration in most studies 104 ; thus, it is uncertain if guided bone regeneration is superior to other nonsurgical or surgical methods for treating periimplantitis. 105 Summary Surgical interventions are more effective in the management of periimplantitis compared with nonsurgical interventions.…”
Section: Resective and Regenerativementioning
confidence: 96%
“…Aim: The aim of the present review by Sahrmann et al (Clin Impl Dent Rel Res 2011;13:46-57) [3] was to systematically evaluate the outcome of GBR using a bone-graft substitute in combination with a membrane on the basis of the parameters to PPD, BOP, and marginal bone loss (BL).…”
Section: Regenerative Treatment Of Peri-implantitis: a Systematic Reviewmentioning
confidence: 99%